DYNAMICS AND LEGAL POLITICAL CHALLENGES OF SIMULTANEOUS REGIONAL ELECTIONS IN INDONESIA TOWARDS EFFICIENCY AND STABILITY - Denny Prabowo; ismaidar, Ismaidar; Tamaulina Br. Sembiring (PT. Sinergi Legal Publisher, 2024)
Regional head elections (Pilkada) in Indonesia have undergone significant changes over time, from the appointment model to direct and simultaneous elections. These changes aim to create a more inclusive, efficient, and stable democratic system. However, simultaneous Pilkada faces various challenges, such as high political costs, inconsistencies in the schedule for regional head elections with the election of DPRD members, and mechanisms for filling regional head positions during the transition period that lack transparency. This study uses normative methods with a legislative and conceptual approach to analyze key regulations, including Law Number 32 of 2004, Law Number 1 of 2015, and Constitutional Court Decision Number 55/PUU-XVII/2019. The results of the study show that direct regional elections provide greater space for public participation, but the high political costs raise the risk of corruption, collusion, and nepotism. On the other hand, regional head elections through the DPRD have the potential to reduce political costs, but are vulnerable to internal politicization. Therefore, reform of simultaneous regional election regulations is needed to align local and national election schedules, strengthen the mechanism for filling regional head positions, and control political costs. In addition, an evaluation of the direct election model by considering the return of regional head elections through the DPRD is one option that is worth studying to create a more efficient and accountable democratic system. The study’s recommendations include strengthening independent oversight, stricter regulation of campaign funding, and comprehensive political education for the public. With the right reforms, simultaneous regional elections can be an effective instrument in supporting local democracy and better local governance in Indonesia.